Forest Composition, Structure and Wildlife Abundance in Mixed-Dipterocarp Forest of Sungai Lalang Forest Reserve, Selangor - Boyd, Sun Fatt (2003)
Tropical rain forest is among the richest ecosystem in the world in terms of flora and fauna diversity. The forest, however, is depleting caused by the encroachment of the forested area such as forest logging. Peninsular Malaysia is practising selective management system (SMS) as one of the sustainable forest management (SFM) in timber harvesting. Such activity would change the forest composition and structure which might also influence to the habitat of plant and animal species. A study was conducted in three different compartments namely Compartment 18 (five-year old logged forest), Compartment 33 (ten-year old logged forest) and Compartment 24 (VJR) at Sungai Lalang Forest Reserve mainly to compare the forest composition and structure. A total of three l-ha plots were made at each compartment and covering three different forest habitats of valley-bottom, mid-slope and ridge-top. All trees 25cm dbh at the three different compartments were tagged and identified up to species level. Tree parameters (tree dbh, tree height and crown width) were also recorded within the study plots for comparison purposes. However, the selected wildlife's composition (primates, pheasants, small mammals and understorey birds) was taken from the previous study as a secondary data. The data's was then compared as descriptive whether the changing of the forest composition and structure influence the presence of wildlife within each compartments.